Assessing EFL Learners' Speaking Self-Efficacy in English Language Education Program Universitas Lancang Kuning - Ulil Albab (ELT-Lectura, 2025)
Speaking self-efficacy is crucial in English as a Foreign Language (EFL) learning, as it significantly influences learners' confidence and performance in oral communication. However, research on the specific level of EFL learners’ speaking self-efficacy and its contributing factors remains limited. This study investigates EFL learners' speaking self-efficacy levels and identifies the key factors shaping their confidence. Using a descriptive quantitative design, data were collected through two validated instruments: the EFL Sources of Speaking Self-Efficacy Scale (EFL-SSSES) and the EFL Learner Speaking Self-Efficacy Scale (EFLSSES). Results reveal that learners exhibit a moderate level of speaking selfefficacy (2.69–3.07). Among the four sources of self-efficacy—Mastery Experience (ME), Vicarious Experience (VE), Social Persuasion (SP), and Physiological Emotional States (PES)—Social Persuasion emerged as the most significant predictor of both Linguistic Self-Efficacy (LSE) (β = .294, p = .025) and Delivery Self-Efficacy (DSE) (β = .310, p = .016). In conclusion, EFL learners possess a healthy level of confidence in their speaking ability, with social persuasion playing a pivotal role. Future research should explore these factors across diverse educational contexts to inform effective teaching strategies.